2015
DOI: 10.1186/s13104-015-1719-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and C viruses infection among military personnel at Bahir Dar Armed Forces General Hospital, Ethiopia

Abstract: BackgroundMilitary personnel are high-risk people for parenteral and sexually transmitted diseases such as hepatitis B virus (HBV) and hepatitis C virus (HCV). Data regarding HBV and HCV prevalence among military personnel in Ethiopia is limited. Hence, the study aimed to determine sero-prevalence and associated risk factors of HBV and HCV among military personnel at Bahir Dar Armed Forces General Hospital, Ethiopia.MethodsA cross-sectional study was conducted in a total of 403 military personnel from February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 24 publications
5
20
4
1
Order By: Relevance
“…In this study co-infection between HBV and HCV infection serologic markers was 0.3% among the general population. This is in contrast to some studies from Ethiopia where no serologic markers for HBV and HCV co-infection was reported [33-35], indicating that co-infection between HBV and HCV may not be uncommon in the areas where both HBV and HCV are endemic. Our finding is supported by findings from many other studies conducted elsewhere which reported dual infection of HBV and HCV: 0.7% in Nigeria among prison inmates [36]; 5.9% and 2.0% in India among patients with chronic liver disease [37] and hemodialysis patients [32] respectively and 7.7% in Mongolia among patients with chronic liver disease [38].…”
Section: Discussioncontrasting
confidence: 98%
“…In this study co-infection between HBV and HCV infection serologic markers was 0.3% among the general population. This is in contrast to some studies from Ethiopia where no serologic markers for HBV and HCV co-infection was reported [33-35], indicating that co-infection between HBV and HCV may not be uncommon in the areas where both HBV and HCV are endemic. Our finding is supported by findings from many other studies conducted elsewhere which reported dual infection of HBV and HCV: 0.7% in Nigeria among prison inmates [36]; 5.9% and 2.0% in India among patients with chronic liver disease [37] and hemodialysis patients [32] respectively and 7.7% in Mongolia among patients with chronic liver disease [38].…”
Section: Discussioncontrasting
confidence: 98%
“…The least infected group (3.1%) were people aged 51 years and above. This finding is in agreement with the report of Bezabeh et al [28] and Birku et al [30] in Ethiopia. According to previous epidemiological studies, there has been a link between age and the prevalence of HBsAg.…”
Section: Discussionsupporting
confidence: 94%
“…The prevalence of HCV infection has been estimated about 3% in the world (13). There are approximately 170 million people with chronic hepatitis C virus (HCV) infection (14,15). HCV infection is a major cause of liver cirrhosis, hepatocellular carcinoma (HCC), and end-stage liver disease (16,17).…”
Section: Contextmentioning
confidence: 99%